Clinical presentation and prognosis in MOG-antibody disease: a UK study - Jurynczyk, M; Messina, S; Woodhall, M; Raza, N; Everett, R; Roca-Fernandez, A; Tackley, G; Hamid, S; Sheard, A; Reynolds, G; Chandratre, S; Hemmingway, C; et al. (Oxford University Press, 2017)
A condition associated with an autoantibody against myelin oligodendrocyte glycoprotein has been recently recognized as a new inflammatory disease of the central nervous system, but the disease course and disability outcomes are largely unknown. In this study we investigated clinical characteristics of myelin oligodendrocyte glycoprotein antibody disease on a large cohort of patients from the United Kingdom We obtained demographic and clinical data on 252 United Kingdom patients positive for serum immunoglobulin G1 myelin oligodendrocyte glycoprotein antibodies as tested by the Autoimmune Neurology Group in Oxford. Disability outcomes and disease course were analysed in more detail in a cohort followed in the Neuromyelitis Optica Oxford service (n = 75), and this included an incident cohort who were diagnosed at disease onset (n = 44) Myelin oligodendrocyte glycoprotein antibody disease affects women (57%) slightly more often than men, shows no ethnic bias and typically presents with isolated optic neuritis (55%, bilateral in almost a half), transverse myelitis (18%) or acute disseminated encephalomyelitis-like presentations (18%). In the total Oxford cohort after a median disease duration of 28 months 47% patients were left with permanent disability in at least one of the following: 16% patients had visual acuity ≤ 6/36 in at least one eye, mobility was limited in 7% (i.e. expanded disability status scale ≥ 4.0), 5% had expanded disability status scale ≥ 6.0, 28% had permanent bladder issues, 20% bowel dysfunction, and 21% of males had erectile dysfunction. Transverse myelitis at onset was a significant predictor of long-term disability. In the incident cohort 36% relapsed after median disease duration of 16 months. The annualized relapse rate was 0.2. Immunosuppression longer than 3 months following the onset attack was associated with a lower risk of a second relapse. Myelin oligodendrocyte glycoprotein antibody disease has a moderate relapse risk, which might be mitigated by medium term immunosuppression at onset. Permanent disability occurs in about half of patients and more often involves sphincter and erectile functions than vision or mobility.